What adolescents living with long-term conditions say about being involved in decision-making about their healthcare: A systematic review and narrative synthesis of preferences and experiences. Issue 10 (October 2018) - Jordan, Amber; Wood, Fiona; Edwards, Adrian; Shepherd, Victoria; Joseph-Williams, Natalie
Highlights: Adolescents with long-term conditions want to "have a say" about their treatment. Parents and health professionals control adolescent involvement in consultations. Involvement preferences between and within individuals can vary substantially. Adolescents often feel that treatment options do not exist. Preferences not being met can be harmful to adolescent well-being and self-efficacy. Abstract: Objective: To understand the preferences and experiences of adolescents (age 10–19) with long-term conditions (LTCs) towards involvement in discussions and decisions regarding management of their condition. Methods: A systematic review and narrative synthesis of mixed-methods, quantitative and qualitative and research was performed. Six databases were searched from inception to March 2017. The quality of the articles was assessed, and relevant data were extracted and coded thematically. Results: The search yielded 27 articles which met the inclusion criteria. Decision-making involvement preferences and experiences were reported from the adolescents' perspectives. Adolescents often report that they do not have any choice of treatment options. Variability in preferences and experiences were found within and between individuals. Mismatches between preferences and experiences are common, and often with negative emotional consequences. Discussion: Adolescent preferences for involvement in the decision-making process are situational and individualistic. Healthcare professionals can encourage involvement by ensuring that adolescents are informed of treatment options, and aware of the value of their contribution. Future research should explore adolescent perceived barriers and facilitators to SDM. Practical implications: Interventions are needed to effectively train HCPs in the delivery of shared decision-making, and to support the participation of adolescents with LTCs in shared decision-making.